Biology Learning Profile with Electronic Student Worksheets Based on Science Process Skills - Suhardi Aldi; Adnan Adnan; Ismail Ismail (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
Learning carried out by educators requires teaching materials. Electronic student worksheets or e-LKPD are one type of teaching material. This study examines the profile of learning biology with e-LKPD. The aim is to obtain an overview of the teaching and learning process and the problems faced by teachers on student worksheets in learning biology material at SMA South Sulawesi. The subjects of this study were 10 schools consisting of 10 teachers of biology subjects. The method used is a survey using a questionnaire and a checklist given to 10 high school teachers in South Sulawesi. The data were obtained by using qualitative descriptive analysis. The results of the descriptive analysis show that the ownership of the LKPD in 10 Biology subject teachers in South Sulawesi is quite high, but the use of the electronic version of the LKPD is still not optimal. LKPD has a varied learning approach, students are motivated and play an active role in learning activities when using LKPD. The cognitive level of the learning objectives of the teacher LKPD is still relatively low, the formulation of objectives in the LKPD which has implications for the application of science process skills is still relatively low, and assignments in the teacher LKPD have not been maximized. The benefit of this research is that it can provide an overview of the learning process and the obstacles experienced by the teacher on the student worksheets.